A Case of Granulosa Cell Tumour with Atypical Presentation (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: Granulosa cell tumour is one of the rare variations of ovarian tumour. As the Granulosa cells secrets Estradiol, the patient with granulosa cell tumour usually present with features of precautious puberty. But our patient present with androgenic features, which inspires us to report this atypical case. Materials and methods: This young patient admitted in BBMH, as a diagnosed case of ovarian tumour with features of virilisation. Evaluation of patient with history taking, clinical examination and investigations are done, and information is noted accordingly. Conclusion: Features of virilisation are a nightmare for a lady of 16 years old. So during management of this patient proper counselling is very crucial and during surgery ovarian reserve should be maintained as far as possible considering her future quality of life and obstetric outcome.J Bangladesh Coll Phys Surg 2019; 37(4): 202-204